Frequency of myotonic dystrophy gene carriers in cataract patients. Issue 3 (March 1996) - Cobo, A M; Poza, J J; Blanco, A; López de Munain, A; Saénz, A; Azpitarte, M; Marchessi, J; Martí Massó, J F
Abstract : DNA samples from 231 unselected patients with cataracts were studied to determine the frequency of the DM mutation in cataract patients. A previous epidemiological study established a high prevalence of DM in the population of Guipúzcoa (Basque Country, Spain), 26.5 cases/100, 000. We have found two carriers (0.9%) of the DM mutation in patients who are not related to any previously known DM family. The screening of the DM mutation in cataract patients should be restricted to young patients or people with multicoloured and iridescent opacities, in which the risk of carrying the DM premutation could be higher. Our results suggest that subjects with 38 to 80 repeats could constitute the genetic reservoir of the DM mutation.